EMPOWERING VOICES: DEVELOPING INNOVATIVE PUBLIC SPEAKING MATERIALS FOR UNIVERSITY STUDENTS - Juliansyah; Bambang Trisno Adi; Alia Afiyati; Rheinatus Alfonsus Beresaby (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
The increasing demand for graduates who are able to communicate effectively in English across different professional domains highlights the need for continuous curriculum evaluation and learning material development. This research is related to the learning outcomes of graduates that have been determined in the English Diploma 3 Program curriculum, especially in the special skills points regarding to oral communication skills in the office, tourism and mass media sectors. In the researcher's understanding, the learning outcomes of graduates must be achieved through various efforts; one of which is the preparation of appropriate learning materials for courses related to communication, one of which is Public Speaking. To be able to compile the learning material in question, complete and precise research has been carried out. Based on this, the appropriate research to be carried out is development research because this research puts ideas into practice as an effort to increase knowledge regarding, for example, curriculum and teaching and learning; then the idea was developed to become a standard model. The results obtained from this research are an increase in what happens in the classroom and understanding of the basis of educational practices implemented. This research also presents ideas about learning materials for Public Speaking courses for students in the English Diploma 3 study program. The expected research results are a more complete set of learning plans and textbooks or modules according to the subjects that are the material of this research.